CITIZEN RESEARCH PRACTICE: LEARNING DATA COLLECTION ON SUMATRAN SLOW LORIS -ELECTRICAL GRID INTERACTION IN LABUHAN RATU VII, EAST LAMPUNG - Elly Lestari Rustiati; Priyambodo Priyambodo; Desta Sandora; Harry Putra Dwitama; Agus Subagyo; Dian Neli Pratiwi; Raden Fadli Bayu; Sunandar Sunandar; Slamet Puji Ariyanto; Tatang Supriyadi (Ann Publisher, 2026)
Background. Supporting the need for the electricity network to carry out daily activities was done by PLN including Penyulang Kecak, the Sribawono Substation for Labuhan Ratu VII, Labuhan Ratu, East Lampung, a WKNP buffer village, the natural habitat of sumatran slow lorises and the electricity grid. Aims. To discussion/interview with village officials related to areas affected by interaction with sumatran slow lorises, from representatives of Labuhan Ratu VII was conducted Methods. Community service in the introduction and collection of community-based data related to the interaction of sumatran slow lorises with the electricity network was carried out by meetings, discussions and companion visits Conclusion. The interaction of sumatran slow loris wildlife and the electrical grid can result its losses both injuries and fatalities. Mitigation conflict tools has been set. Strengthening the local communities supports, companionship on citizen research, community-based data collection assistance was done in Labuhan Ratu VII, East Lampung. Knowledge on sumatran slow loris, electrical grid and conflict mitigation was engaged. Implementation. Data collection based on rapid assesment includes the research perception, document and data collection in the field was introduced and applied